The Structural Equation Modeling of factors Influencing University students' Social Welfare Behavior Intention in Taiyuan region, China - Zhang, Min; Sigdel, Bijay; Phromphithakkul, Wasin (วารสารวิชาการ การจัดการภาครัฐและเอกชน, 2023)
Social welfare practice is an important way to realize the educational goal of "practice education" in Chinese colleges and universities. The formation mechanism of university students' social welfare practice behavior intention has guiding significance for colleges and universities to carry out social welfare practice. This research adopted the theory of planned behavior as the basic framework, then added public welfare study variables and built a confirmatory factor model of the literature research results. The questionnaire survey collected 467 sets of questionnaires. Subsequently, a structural equation model was created and the assumptions were examined to analyze the influence of various factors such as, public welfare education, behavioral attitudes, subjective norms and perceived behavioral control on intentions in social welfare behavior of university students. This research could be concluded that behavioral attitude, subjective norm, and perceived behavioral control had a significant direct impact on university students' social welfare behavioral intentions, on the other hand, public welfare education indirectly affected behavioral intentions through behavioral attitudes, subjective norms, and perceived behavioral control. We should strengthen the factors affecting university students' public welfare behavioral intentions in various aspects in order to stimulate students' motivation to participate in public welfare activities and promote active participation in public health activities among university students.